NSRRC Hosts the FEL Winter School. Issue 3 (3rd May 2016) - Lin, Diana; Chu, Becky
Abstract : With continuous support from professors and scientists from the Stanford Linear Accelerator Center (SLAC), Indiana University, National Tsing Hua University, and National Chiao Tung University, the National Synchrotron Radiation Research Center (NSRRC) held the Free Electron Laser (FEL) Winter School on January 18–22, 2016, in Hsinchu, Taiwan for the fourth consecutive year. The five-day program was sponsored by the Physics Research Promotion Center (PRPC) under the Ministry of Science and Technology (MOST) and organized by the NSRRC. Thirty-four applicants were accepted, including 19 undergraduate students, 12 graduate students in master's programs, and three doctoral students.